PERAN KEPALA SEKOLAH DALAM MENINGKATKAN PENGGUNAAN TEKNOLOGI DALAM PEMBELAJARAN - Nur Nabila (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The important role of the principal in improving the application of technology in the teaching and learning process amidst the rapid evolution of knowledge, technology, and information, especially in the digital age and the 4.0 revolution. The education system in Indonesia needs to continue to adapt and incorporate information and communication technology (ICT) into all aspects of education to improve accessibility, adaptability, and quality of education. The goal of education is not only to produce students who are academically intelligent, but also have high ethics, and are ready to face the challenges of the digital era. This study uses a literature review method, the data obtained are in the form of journals and books on relevant topics. The principal, as the manager and leader of the institution, is responsible for planning, organizing, implementing, supervising, and controlling all educational processes in the school. The quality and success of a school are greatly influenced by the leadership of the principal. The principal needs to be an active digital leader, formulate comprehensive plans, and create a culture of innovation to integrate technology into the curriculum.